Mitigating Emissions in India: Accounting for the Role of Real Income, Renewable Energy Consumption and Investment in Energy - Bekun, Festus Victor (International Journal of Energy Economics and Policy, 2022)
Accomplishing environmental sustainability has become a global initiative whilst addressing climate change and its effects. Thus, there is a necessity for innovation on part of economies as they seek energy for sustainable development. Thus, we explore the case of India a highly industrialized and heavy emitter of carbon emission. To this end, this study explores the effect of renewable energy, non-renewable, economic growth, and investment in the energy sector on CO2 emission in the Indian economy. Canonical Cointegration Regression (CCR), Fully Modified Least Squares (FMOLS) and Dynamic Least Squares (DOLS) were used to access the long-run elasticity of the variables as well as Granger Causality analysis to detect the direction of causality relationship among the highlighted variables. Empirical regression shows a negative relation between CO2 emission and renewable energy. Thus, suggesting that renewable energy serves as a panacea for sustainable development in the face of economic growth trajectory. However, there was a positive relationship between CO2 emission and both non-renewable and real GDP growth. On the Granger analysis, we observe a one-way causality among renewable energy consumption and CO2 emission, economic development, and energy investment. These outcomes have far-reaching policy direction of environmental sustainability target in Indian economy.